Importance of Afghanistan for Regional Security in South and East Asia - N. Rawan; O. E. Grishin (Проблемы постсоветского пространства)
In this article, the importance ofAfghanistanfor South andEast Asiaand for regional security is assessed.Asiaas a whole and the south Asian region in particular is playing an increasingly important role in world politics and economy. It’s believed that south Asia is moving forward and will be in a much better position both in politics and economy in the future of Asia and world. The region has been characterized by the dynamic inter-play of security, economic and diplomatic factors reinforcing each other owing to the complex nature of territorial claims and religious extremist activities.Afghanistanstrategic location is so important for south Asian countries likePakistan,Indiaand also forChina,IranandRussiastability and security in the region. AsAfghanistanis still a safe haven for international terrorists’ groups and Taliban, therefore it’s a serious threat to the region and world. Due to the geo-strategic Location of Afghanistan any problem will affect the region stability and security as it did in the past too. Further Successive regimes inPakistanhave tried their best to impose a favorable government inAfghanistanbut those policies harmed them only. ForChina, the importance ofAfghanistanbecomes evident from the internal security in Xinjiang region.Iranwould like to seeAfghanistanfree fromUSexistence. From other sideRussiaworry about the inflow of opium and other narcotics fromAfghanistanto the centralAsia.